Wire- and Ultrasound-Guided Localization: A Novel Technique for Excision of Nonpalpable Breast Tumors. (July 2020) - Khare, Siddhant; Singh, Tulika; Santosh, Irrinki; Laroiya, Ishita; Singh, Gurpreet
Background: Excision of nonpalpable breast lesions requires intraoperative guidance. Wire-guided localization and intraoperative ultrasounds have been used successfully but suffer from some disadvantages. We describe a new modification of the standard technique using a combination of preoperative ultrasound in conjunction with standard wire-guided localization. Methods: Wire and ultrasound-guided localization (WUGL) technique was used for the excision of nonpalpable breast lesions. Results: Sixty-nine patients with nonpalpable breast lesions were subjected to excision using WUGL, out of whom 63 patients had a preoperative diagnosis of invasive/noninvasive breast cancer. Six patients had a preoperative diagnosis of benign lesions, out of which 3 patients were converted to invasive breast cancer on final pathology. Only 1 patient had positive margin. Conclusions: WUGL is a technique that uses a combination of well-accepted and easily available techniques. It has given good results and has the potential for widespread acceptance in resource-constrained situations.